The relationship of hematological parameters with adaptation and reproduction in sheep : a review study - al-Thuwayni, Tahrir Muhammad (Iraqi journal of veterinary sciences, 2021)
تمتلك الأغنام خصائص مرغوبة للمزارعين مثل مقاومة الأمراض، و التأقلم الجيد مع التقلبات البيئية، و تحمل الطقس القاسي. قد يعود هذا، جزئيا، إلى خصائص الدم و الأنواع مختلفة من الهيموغلوبين، و التي تتفاعل بشكل مختلف مع التغيرات الخارجية؛ مظهرة قدرة تكاثرية مختلفة في ظروف بيئية معينة. هدفت هذه المراجعة إلى التحري عن تأثير معايير الدم و أنواع الهيموغلوبين على التكيف و الأداء التكاثري للأغنام. المعايير الدموية هي أدوات مفيدة للكشف عن التكيف و الحالة الفسيولوجية لهذه الحيوانات. يعتمد تكاثر الأغنام على قدرة كل نوع و سلالة على التأقلم مع الظروف البيئية المختلفة. بالإضافة الى ذلك، ارتبطت أنواع الهيموغلوبين مع التكيف البيئي و الصفات الفسيولوجية للأغنام. لذلك، قدمت هذه المراجعة معلومات مفيدة عن ارتباط معايير الدم و أنواع الهيموغلوبين في الأغنام مع التكيف و الأداء التكاثري و يمكن استخدامها كأدوات حيوية تساعد في تحديد الأنواع أو سلالات الأغنام الأكثر تكيفا مع بيئات معينة أو لديها المزيد من القدرة على التكاثر. Sheep possess desirable characteristics for farmers such as resistance to disease, good acclimation to environmental fluctuations, and endurance to extreme weather. This may, in part, be due to hematology characteristics and various types of hemoglobin that interact differently to external changes; displaying various reproductive ability in certain environmental conditions. This review aims to investigate the effect of hematology parameters and hemoglobin types on the adaptation and reproductive performance of sheep. Hematological parameters are useful tools for the detection of adaptation and physiological traits of these animals. The reproduction of sheep has depended on the ability of each type and breed to acclimate to different environmental conditions. In addition, hemoglobin types have also been correlated with the environmental adaptability and physiological traits of sheep. Thus, the present review provides useful information on the association of hematology parameters and hemoglobin types in sheep with adaptation and reproductive performance, and could be used as vital tools that help in determining the species or breed of sheep that are more adapted to certain environments or have more reproductive potential.